Population Aging and Health Trajectories at Older Ages. (1st June 2017) - Vogelsang, Eric M; Raymo, James M; Liang, Jersey; Kobayashi, Erika; Fukaya, Taro
Abstract: Objective: This study examines relationships between municipal age structure and two types of self-rated health: general (SRH) and comparison with similar-aged peers (C-SRH). Methods: Using a national sample of almost 5, 000 Japanese older adults over two decades, we employ hierarchical growth curve models to estimate health trajectories. For municipal age structure, we consider both the relative prevalence of elderly adults in the local population and the pace of aging over time. Results: Living in the oldest municipalities was generally associated with worse health, particularly between the ages of 70 and 80 years. For SRH, the speed of municipal population aging was also independently associated with worse health. For C-SRH, worse health in older areas was partially explained by less favorable economic conditions in those municipalities. Results also suggest that higher levels of employment and social integration among older adults living in the oldest municipalities operate in the opposite direction. That is, these attributes partially "protect" individuals from other factors that contribute to worse health. Discussion: Relative differences in municipal age structure and the pace of population aging are largely unexplored and potentially important correlates of older adult health. This line of research is increasingly salient in a world with substantial and growing regional variation in population aging.